A tutorial on the synthesis and applications of molecularly imprinted polymers in analytical chemistry - N.P. Kalogiouri; A. Kabir; K.G. Furton; V.F. Samanidou (Journal of Chromatography Open)
Molecularly imprinted polymers (MIPs) have emerged as highly selective sorbents with tailor-made recognition sites complementary to target analytes in terms of shape, size, and functional groups. This tutorial provides a comprehensive overview of the principles, synthesis strategies, and analytical applications of MIPs, with a focus on their utility in sample preparation, separation, and detection. Various imprinting techniques—such as bulk, surface, and nanoimprinting—are discussed alongside advances in green synthesis and novel monomer-template systems. Emphasis is placed on the integration of MIPs with chromatographic and spectrometric platforms, particularly in complex matrices relevant to environmental, pharmaceutical, food, and clinical analysis. The tutorial illustrates the practical considerations for designing and optimizing MIP-based methods, including template selection, polymerization conditions, and reusability, reflecting recent and relevant advances of the last ten years This tutorial aims to guide researchers and analysts in leveraging the unique properties of MIPs to enhance selectivity, sensitivity, and sustainability in modern analytical chemistry.